Battles of Pleven: A Glorious Defeat in Military History - Umut Akcakaya (Journal of Universal History Studies)
The Ottoman-Russian War of 1877-1878 was one of the most important events that marked the last century of the Ottoman Empire. In this war, the armies of both sides faced each other on the Balkan and Caucasian fronts, and the Balkan Front was the war’s center of gravity. Having crossed the Danube, the Russian army quickly advanced south and captured the Shipka pass. Thus, the road to Istanbul was opened for the Russians. In the same days, the Vidin Corps under the command of Osman Pasha came to Pleven and took positions in the city. Before descending to the south of the Balkan Mountains, the Russians decided to capture Pleven and attacked the city three times. In Pleven, the Ottoman forces repelled these attacks and stopped the Russian operation for five months. In this way, they prevented a defeat that would come much earlier for the Ottoman Empire. Osman Pasha halted the Russian army by defending Pleven for five months. In this way, he allowed the Ottoman Commander-in-Chief to change the war’s fate. The Ottoman command, however, could not be able to use this opportunity. Finally, the supplies in the city were exhausted and there was no possibility of defense. Osman Pasha decided to break the siege with a breaktrough operation, but was wounded and had to surrender. Shortly after the fall of Pleven, the Russian armies came to Istanbul and the war ended. Despite the defeat, the defense of Pleven had a great impact and was appreciated all over the world.